Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M.; Kemmelmeier, Markus; Gupta, Vishal K.; McKelvey, William (Understanding Women's Entrepreneurship in a Gendered Context, 2021)
Keywords: dept.mgt; peer-reviewed

Staying Alive: Leadership in COVID-19 World - Stewart, Carol (Journal of Leadership, Accountability & Ethics, 2021)
While this unprecedented time of COVID-19 has resulted in financial loss for many companies, it's also produced new leadership opportunities. Remote work, at-home schooling, and socially-distancing are a few examples of the new norm and new business possibilities. As crisis proverbially breeds innovation, new businesses have already sprung up around the world in support of growing demands. History shows this growth in entrepreneurial endeavors to be a trend during times of economic downturn. More than half of 2009 Fortune 500 list and just under half of 2008's Inc. list were created during a recession or bear market. Challenging economic times often seed the growth of entrepreneurial capitalism. One reason for this growth is that startup companies begun during times of high stress tend to be capable of operating in less favorable conditions. In times of economic upheaval, even mature businesses with longer history and deeper pockets require special leadership to 'pivot' their operational strategies to stay viable. This paper explores effective leadership theories to explain the success during uncertain times.
Keywords: BEAR markets; COVID-19; LEADERSHIP; NEW business enterprises; SITUATIONAL leadership theory; TELECOMMUTING; dept.mgt; entrepreneurship; leadership; pandemic; peer-reviewed; pivoting; situational leadership

Improving school performance and student academic orientation: the role of safety-oriented knowledge management and diversity - Birasnav, M.; Gantasala, Prabhakar Venugopal; Gantasala, Swapna Bhargavi (VINE Journal of Information and Knowledge Management Systems, 2021)
Purpose The purpose of this study is to examine the influence of the implementation of safety-oriented knowledge management (KM) processes and student diversity acceptance in schools and the interaction effect of safety-oriented KM processes and student diversity acceptance over school performance and student academic orientation. Design/methodology/approach Responses of 977 American schools available in the database of the National Center for Education Statistics were analyzed using hierarchical regression analyses. Findings Results show that implementation of safety-oriented KM processes and diversity acceptance in schools have varying effects on school performance and student academic orientation. The impact of knowledge acquisition from parents on the academic achievement of students is positive and stronger in schools that are low in student diversity acceptance than schools that are high in student diversity acceptance. Originality/value This study adds value to the KM literature by exploring how KM processes are executed in American schools to improve their performance and students’ academic orientation and how diversity among students alters the strength of the relationships.
Keywords: Diversity acceptance; Knowledge management processes; School performance; School safety; Student academic orientation; dept.mgt; peer-reviewed

Ease of market entry of Indian startups: formal and informal institutional influences - Scillitoe, Joanne L.; Birasnav, Muthuraj (South Asian Journal of Business Studies, 2021)
Purpose The purpose of this study offers a theoretical model, hypotheses and empirical analyses of how formal and informal institutions influence the ease of market entry of startups in the context of India. Design/methodology/approach A theoretical model based upon institutional and market entry theories is presented with hypotheses. Structural equation modeling is used to test the hypotheses. Findings Results of the study suggest that college preparations and a culture of creativity and innovation are positively related to ease of market entry by Indian startups. A culture of personal success is negatively related to ease of market entry. Government assistance related to ease of market entry is not significant. Originality/value This paper offers a new perspective, linking formal and informal institutional influences to startup ease of market entry. In addition, informal institutions are viewed from the cultures of personal success and creativity/innovation within the entrepreneurial domain, which is also new to the literature. This paper offers specific insights in the context of India startups and offers some interesting findings that can contribution to the literature, policy and practice.
Keywords: Culture; Entrepreneurship; India; Institutions; Market entry; Startup; dept.mgt; peer-reviewed

The Reciprocal Relationship between Containers Overboard and Climate Change - Daniel, J.; Stapleton, K. A.; Stapleton, D.; Nandialath, A.; Franklin, D. (Journal of Transportation Law, Logistics, and Policy, 2021)
Not only does the flotsam and jetsam in the world’s oceans seem to be impacting the health of the world’s oceans and seas, but it appears that the warming climate and increasing CO2 emissions are impacting the global trade lanes evidenced by a greater-than-average number of lost maritime containers due to resultant rougher seas and stronger storms. We elucidate the evolution of containerized shipping and discuss the impact lost containers have on the seas and dangers to other ocean-going vessels. We also note the reciprocal effects between climate change and lost containers. The intent of our article is to shed light on these issues and we hope it sparks future research examining causal factors and their potential solutions.
Keywords: dept.mgt; peer-reviewed

The Crisis of Danbury Fair Mall - Ahn, Jin Sun; Chung, Hanyong; Kim, Jung Hoon; Kim, Youngbin; Shin, Natalie Jungyoun (Journal of Marketing Development and Competitiveness, 2021)
This case describes the difficult financial situation of Danbury Fair Mall, which is the second biggest shopping mall in Connecticut. After World War II, the shopping mall business had grown fast especially in suburban areas of the U.S. However, the increasing popularity of online shopping caused extensive damage to shopping malls. This case will provide students the chance to think about the past, the present, and the future of the shopping mall industry in the U.S
Keywords: Connecticut; dept.acc; dept.mgt; peer-reviewed; ⛔ No DOI found

The Detrimental Effects of Ethical Incongruence in Teams: An Interactionist Perspective of Ethical Fit on Relationship Conflict and Information Sharing - Shin, Natalie J.; Ziegert, Jonathan C.; Muethel, Miriam (Journal of Business Ethics, 2021)
Building from an interactionist view of ethics, this study sought to integrate individual and contextual factors for understanding ethical perceptions in teams. Given the proximal nature of team members, this study specifically explored how individuals comparatively evaluate their own ethical behaviors and team members’ ethical behaviors to arrive at a perception of ethical person–group (P–G) fit within a team. Grounding our theoretical arguments in relational schemas theory (Baldwin, Psychological Bulletin 112:461–484, 1992), we demonstrate that interpersonal ethical perceptions can have distal impacts on perceptions of team functioning. The results support the hypotheses that a perceived ethical incongruence between the self and other team members (i.e., lack of ethical P–G fit) negatively influenced perceptions of relationship conflict and ultimately information sharing. By exploring individual and team level aspects of ethics concurrently, we contribute to a deeper understanding of contextual forces in ethics through an interactionist approach.
Keywords: dept.mgt; peer-reviewed

Using contemplative photography in transformative sustainability management education: Pedagogical applications in the united states, russia and germany - Yang, Charlie; Ivanova, Ekaterina; Hufnagel, Julia (The International Journal of Management Education, 2021)
Developing a sustainability mindset requires a transdisciplinary approach to business education that integrates a rational-analytic mode of thinking and an emotive-holistic understanding of the human mind. In order to cultivate the sustainability mindset of business students, we have designed a contemplative art-based project involving the creation of an electronic portfolio which consists of a student's digital photographs. We have integrated it into our teaching of management courses in the United States, Russia, and Germany, respectively. The project aims to enable business students to become more visually attentive and environmentally conscious, so that they will pay close attention to the process of building more sustainable relationships within their natural and social environments. From the interpretative phenomenological perspective, we have analyzed the students' e-portfolios in order to understand how business students make sense of environmental and human sustainability. While envisioning more transformative sustainability management education, we have also discussed the pedagogical implications of making the e-portfolios for enhancing the students' understanding of the sustainability mindset. © 2021 Elsevier Ltd
Keywords: dept.mgt; peer-reviewed

Socio-economic impacts of the Great Lakes restoration initiative - Liesch, Matthew; Graziano, Marcello (Geographical Review, 2021)
Interviews illuminate impacts of the Great Lakes Restoration Initiative (GLRI), a United States’ federal program designed to improve the Great Lakes by restoring the region’s most polluted harbors and coastal landscapes. To see how GLRI funds caused changes in the built environment and to attitudes toward place, semi-structured interviews were conducted with private- and public-sector leaders. Case studies are four EPA-designated Areas of Concern receiving substantial GLRI funds in Buffalo, New York; Duluth-Superior, Minnesota and Wisconsin; Muskegon, Michigan, and Sheboygan, Wisconsin. Results show that GLRI serves as a catalyst in three principal ways: The program leveraged local and state funds, both private and public. GLRI also leads to greater socio-spatial consciousness regarding rehabilitated places. Also, GLRI had led to stronger and deeper senses of place. This study reveals interviews help to calculate a more holistic return on investment for a prominent federal program. This study offers a way forward for ecosystem services research to take a more holistic view than has traditionally been done, in that semi-structured interviews illuminate impacts that traditional economic modeling alone cannot. Concurrently, this research is an example of how a prominent federal program affects community perceptions integral to holistic coastal planning processes. © Copyright © 2021 by the American Geographical Society of New York.
Keywords: dept.mgt; peer-reviewed

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test. - Lunn, William R.; Axtell, Robert S. (Journal of strength and conditioning research, 2021)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Environmental performance, environmental management and company valuation - Abrams, Roy; Han, Seungmin; Tanzeeb Hossain, Mehdi (Journal of Global Responsibility, 2021)
Purpose: This paper aims to investigate the relationship between environmental performance and management and company valuation. With a specific focus on company valuation, this study shows how a firm’s environmental activities, including its environmental management practices, are perceived and valued by its stockholders. Design/methodology/approach: Newsweek’s green ranking data between 2014 and 2016 were used to support this analysis. Environmental performances and environmental management practices of 345 Fortune 500 companies from various industries were included in the data set. Findings: The analysis finds higher valuations for US companies that are more efficient in managing greenhouse gas emissions. In addition, it empirically shows that investors place a higher value on companies with the following environment-related management policies: initiatives that reward top management for achieving environmental goals and third-party auditing of environmental performance. Originality/value: By incorporating corporate environmental management practices as an additional environmental performance criterion, this research fills a gap in the literature on the potential relationship between corporate environmental performance and company valuation. © 2021, Emerald Publishing Limited.
Keywords: dept.mgt; peer-reviewed

Legacy and shockwaves: A spatial analysis of strengthening resilience of the power grid in Connecticut - Gallaher, Adam; Graziano, Marcello; Fiaschetti, Maurizio (Energy Policy, 2021)
Grid resilience and reliability are pivotal in the transition to low and zero carbon energy systems. Tree-trimming operations (TTOs) have become a pivotal tool for increasing the resilience power grids, especially in highly forested regions. Building on recent literature, we aim at assessing the temporal and spatial extents of the benefits that TTOs produce on the grid from three perspectives: the frequency, extent, and duration of outages. We use a unique dataset provided by Eversource Energy, New England's largest utility company, with outage events from 2009 to 2015. We employ spatial econometrics to investigate both the legacy and spatial extent of TTOs. Our results show TTOs benefits occur for all three metrics for at least 4 years, and benefits spillover to up to 2 km throughout the treated areas, with significant spatial spillovers across the state greater than direct effects. Implications lead to supporting TTOs as part of the hardening policies for utility companies, especially as home-based activities increase in importance in a post-COVID19 world. © 2021 Elsevier Ltd
Keywords: COVID-19; Connecticut; Economics; Electric power transmission networks; Energy transitions; Low carbon; Outages; Power grids; Spatial analysis; Spatial extent; Spatial modelling; Statistics; Tree trimmings; Trimming; Trimming operations; United States; Utilities companies; Vegetation management; atmospheric electricity; data set; dept.mgt; econometrics; electricity; smart grid; spatiotemporal analysis; utility sector

Integrating returns and costs in examining faster firm speed - Lee, Minjae (Academy of Management Proceedings, 2021)
Keywords: dept.mgt

A data-based approach to identifying regional typologies and exemplars across the urban–rural gradient in Europe using affinity propagation - Fiaschetti, Maurizio; Graziano, Marcello; Heumann, Benjamin W. (Regional Studies, 2021)
We apply recent developments in data-mining and statistics, using affinity propagation (AP) to identify regional typologies in the European Union (EU) and characterize major factors between rural–rural and rural–urban regional differences, without predetermined thresholds. We identify a representative ‘exemplar’ within each cluster using the drivers of Copus enriched with climate and land-cover/land-use variables to provide geographical context and pinpoint differences driven by natural and human–natural landscapes. Building upon the works of Dijkstra and the Eudora Project, we expand the dimensions of regional differences, introducing a threshold-less, data-driven model able to identify exemplars, and the main characteristics of each cluster or regional typology. © 2021 Regional Studies Association.
Keywords: Europe; European Union; data mining; dept.mgt; economic development; peer-reviewed; regional development; urban-rural migration

A Self-Determination Approach to Understanding Individual Values as an Interaction Condition on Employees' Innovative Work Behavior in the High-Tech Industry - Wang, Zheni; Gao, Mengchan; Panaccio, Alexandra (Journal of Creative Behavior, 2021)
Drawing on self-determination theory (SDT; E.L. Deci & R.M. Ryan, 1985, 2000) and using corporate samples (N = 284; 63% Male; Mean Age = 34, SD = 6.09) from high-tech firms in China, this empirical study explored the path model from satisfaction of the basic psychological needs for autonomy, competence, and relatedness, through autonomous motivation to employees' innovative work behavior (“IWB”; J. De Jong & D. Den Hartog, 2010). It also simultaneously examined the interactions between autonomous work motivation and individual values (collectivism, H.C. Triandis (1995); uncertainty avoidance, R. J. House, P. J. Hanges, M. Javidan, P. W. Dorfman, & V. Gupta (2004); and power distance, J. Farh, R.D. Hackett, & J. Liang (2007)) in the conditioned path model. The regression results obtained from conditional PROCESS analysis (A.F. Hayes, 2013, 2018) suggest that basic psychological needs satisfaction is positively related to employees' IWB via autonomous motivation, but that these indirect effects were weaker when employees' power distance value orientation was high. Implications, limitations, and future research directions are discussed. © 2020 by the Creative Education Foundation, Inc.
Keywords: dept.mgt; peer-reviewed